The role of astrocytes in CNS tumors: pre-clinical models and novel imaging approaches - O'Brien, Emma R.; Howarth, Clare; Sibson, Nicola R. (Frontiers in Cellular Neuroscience, 2013)
Brain metastasis is a significant clinical problem, yet the mechanisms governing tumour cell extravasation across the blood-brain barrier and CNS colonisation are unclear. Astrocytes are increasingly implicated in the pathogenesis of brain metastasis but in vitro work suggests both tumoricidal and tumour-promoting roles for astrocyte-derived molecules. Also, the involvement of astrogliosis in primary brain tumour progression is under much investigation. However, translation of in vitro findings into in vivo and clinical settings has not been realised. Increasingly sophisticated resources, such as transgenic models and imaging technologies aimed at astrocyte-specific markers, will enable better characterisation of astrocyte function in CNS tumours. Techniques such bioluminescence and in vivo fluorescent cell labelling have potential for understanding the real-time responses of astrocytes to tumour burden. Transgenic models targeting signalling pathways involved in the astrocytic response also hold great promise, allowing translation of in vitro mechanistic findings into pre-clinical models. The challenging nature of in vivo CNS work has slowed progress in this area. Nonetheless, there has been a surge of interest in generating pre-clinical models, yielding insights into cell extravasation across the blood brain barrier, as well as immune cell recruitment to the parenchyma. While the function of astrocytes in the tumour microenvironment is still unknown, the relationship between astrogliosis and tumour growth is evident. Here, we review the role of astrogliosis in both primary and secondary brain tumours and outline the potential for the use of novel imaging modalities in research and clinical settings. These imaging approaches have the potential to enhance our understanding of the local host response to tumour progression in the brain, as well as providing new, more sensitive diagnostic imaging methods.